Integrated modelling and multiscale gyrokinetic validation study of ETG turbulence in a JET hybrid H-mode scenario. (1st August 2022) - Citrin, J.; Maeyama, S.; Angioni, C.; Bonanomi, N.; Bourdelle, C.; Casson, F.J.; Fable, E.; Görler, T.; Mantica, P.; Mariani, A.; Sertoli, M.; Staebler, G.; et al.
Abstract: Previous studies with first-principle-based integrated modelling suggested that electron temperature gradient (ETG) turbulence may lead to an anti-gyroBohm isotope scaling in JET high-performance hybrid H-mode scenarios. A dedicated comparison study against higher-fidelity turbulence modelling invalidates this claim. Ion-scale turbulence with magnetic field perturbations included, can match the power balance fluxes within temperature gradient error margins. Multiscale gyrokinetic simulations from two distinct codes produce no significant ETG heat flux, demonstrating that simple rules-of-thumb are insufficient criteria for its onset.